1968
DOI: 10.1113/jphysiol.1968.sp008527
|View full text |Cite
|
Sign up to set email alerts
|

Firing patterns of gastrocnemius motor units in the decerebrate cat

Abstract: SUMMARY1. The patterns of medial gastrocnemius (MG) motor unit firing in response to MG muscle stretch have been studied in decerebrate cats, using intracellular recording techniques. In most of the units, the motoneurone axonal conduction velocity and cell input resistance were measured, and the maximum amplitude and wave form of the group Ia composite EPSP evoked by MG nerve stimulation were determined. The mechanical properties of the muscle unit portion of each motor unit were also studied.2. Motor unit fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0

Year Published

1968
1968
2012
2012

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 155 publications
(74 citation statements)
references
References 38 publications
3
71
0
Order By: Relevance
“…The intermittent behavior of these phasic units is governed inherently by their low oxidative metabolism (Bradacs et al 1997). Postural motor units, however, are small, highly excitable units and are thus capable of discharging tonically (Burke 1968). The intermittency of the postural MG motor units, then, is not a consequence of their physiological inability to sustain firing.…”
Section: When Does Recruitment Occur? To What Theories Of Control Of mentioning
confidence: 99%
“…The intermittent behavior of these phasic units is governed inherently by their low oxidative metabolism (Bradacs et al 1997). Postural motor units, however, are small, highly excitable units and are thus capable of discharging tonically (Burke 1968). The intermittency of the postural MG motor units, then, is not a consequence of their physiological inability to sustain firing.…”
Section: When Does Recruitment Occur? To What Theories Of Control Of mentioning
confidence: 99%
“…In the present paper an attempt has been made to examine what may be regarded as an extrinsic characteristic of motor units, that is, the relative amount and organization of synaptic input to triceps surae units. This study has been limited to the monosynaptic group I a input, both for technical simplicity and because this excitatory input to extensor cells is of considerable interest as it relates to motoneurone properties (see Eccles, Eccles & Lundberg, 1957a;Mendell & Henneman, 1967) and to motor unit firing patterns (see Denny-Brown, 1929;Granit, Henatsch & Steg, 1956; Granit, Phillips, Skoglund & Steg 1957;Henneman, Somjen & Carpenter, 1965a, b; Burke, 1968).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the firing rate of a motoneurone, which is controlled by the duration of afterhyperpolarization, is matched to the twitch duration of its muscle fibres (Eccles, Eccles & Lundberg, 1958). The maximum rates of motoneurone discharge obtained by stretching the muscle or by tetanization of its afferents are 0022-3751/79/3020-0586 $01.50 © 1979 The Physiological Society higher for fast twitch motor units than for slow ones, but not high enough to give a completely fused contraction of any type of motor unit (Burke, 1968).…”
Section: Introductionmentioning
confidence: 99%